Angelman syndrome in adolescence and adulthood: A retrospective chart review of 53 cases. Issue 6 (25th April 2018) - Prasad, Ankita; Grocott, Olivia; Parkin, Kimberly; Larson, Anna; Thibert, Ronald L.
Abstract : Angelman syndrome is a neurogenetic disorder with varying clinical presentations and symptoms as the individual ages. The goal of this study was to characterize changes over time in the natural history of this syndrome in a large population. We reviewed the medical records of the 53 patients who were born prior to 2000 and seen at the Angelman Syndrome Clinic at Massachusetts General Hospital to assess neurological, sleep, behavioral, gastrointestinal, orthopedic, and ophthalmologic functioning. The average age of this cohort was 24 years. Active seizures were present in 35%, nonepileptic myoclonus in 42%, and clinically significant tremors in 55%. Anxiety was present in 57%, increasing to 71% in those ages 26–43 years. In terms of sleep, 56% reported 8 hr of sleep or more, although 43% reported frequent nocturnal awakenings. Gastrointestinal issues remain problematic with 81% having constipation and 53% gastroesophageal reflux. The majority lived in a parent's home and remained independently mobile, though scoliosis was reportedly present in 30%, and 20% had reported low bone density/osteoporosis. The results of this study suggest that the prevalence of active seizures may decrease in adulthood but that the prevalence of movement disorders such as tremor and nonepileptic myoclonus may increase. Anxiety increases significantly as individuals age while defiant behaviors appear to decrease. Sleep dysfunction typically improves as compared to childhood but remains a significant issue for many adults. Other areas that require monitoring into adulthood include gastrointestinal dysfunction, and orthopedic/mobility issues, such as reported scoliosis and bone density, and ophthalmologic disorders.